The Development of Biology E-Pocket Book to Improve Senior High School Students’ Biology Literacy Ability - Mega Candra Kumalasari; Joko Waluyo; Iis Nur Asyiah (Green Publisher Indonesia, 2022)
This research aimed at improving biology literacy ability based on HOTS (Higher Order Thinking Skill) by using E-pocket book learning media. This research employed a research and development (R&D) method, which was used as actual proof in improving a learning media of HOTS-based E-pocket book. There were 10 schools, including state or private schools, and 10 biology teachers as need analysis involved in this study. A needs assessment was conducted by using a questionnaire generated in Google form. The result of the needs assessment showed that teachers understood the HOTS learning process of 90%, HOTS learning material of 80%, and the teachers’ knowledge on E-pocket book learning media of 50%. Therefore, all of the teachers (100%) agreed if E-pocket book learning media is implemented for the students and if the learning media that can improve the students’ biology literacy should be developed.